ACUTE RESPIRATORY DISTRESS SYNDROME DAN ACUTE PNEUMONIA PADA NEAR DROWNING:SEBUAH LAPORAN KASUS - Michelle Prinka Adyana (E-Jurnal Medika Udayana, 2014)
Near drowning is a condition in which the victim survived the first 24 hours. The WorldHealth Organization (WHO ) , recorded worldwide in 2000 there were 400,000 incidentdrowned accidentally . That is, this figure ranks second only to traffic accidents.Aspiration pneumonia is a complication of near drwoning which occurred in 80 % ofcases of near drowning, while 50 % of patients sink into acute respiratory distresssyndrome ( ARDS ) . This case report discusses the acute respiratory distress syndromeand acute pneumonia in near drowning 24 years old , who had drowned at the beach for± 15 minutes , the chest x - ray obtained pulmonary edema dd / lung pnuemonia therepneuomothorax . Examination of multislice spiral computed tomography ( MSCT )bilateral pneumothorax Thorax obtained major and minor fisuura right and left majorfissure , pneumomediastinum , pulmonary pneumonia contusio / suspected aspirationpneumonia , emphysema subcutis . In intensive care patients conducted for 9 days andreturn to akitivitas everyday